Research Status of Preparation Technology of Tungsten-based Coatings - Tian, Lili (International Journal of Mechanical and Electrical Engineering, 2026)
Due to its excellent properties such as high melting point, high hardness, strong corrosion resistance and low saturated vapor pressure, refractory metal W has been widely used in aerospace, nuclear industry, electronics and other fields. However, due to the scarcity and high cost of W resources, its large-scale application in large or complex structural components is severely restricted. In this context, the popularization and use of surface coating technology can not only prepare high-performance W-based coatings on the surface of low-cost substrates, but also solve the cost problem of W resource shortage. At present, the preparation technology of W-based coatings has formed a diversified pattern. Physical vapor deposition, chemical vapor deposition, spraying technology, laser cladding technology and electroplating and other methods each have unique advantages and applicable scenarios. This article will systematically sort out the preparation technology, performance optimization strategies and application status of tungsten-based coatings, analyze the existing problems in current research, and look forward to its future development direction.